Study protocol for the SARON trial: a multicentre, randomised controlled phase III trial comparing the addition of stereotactic ablative radiotherapy and radical radiotherapy with standard chemotherapy alone for oligometastatic non-small cell lung cancer. Issue 4 (17th April 2018) - Conibear, John; Chia, Brendan; Ngai, Yenting; Bates, Andrew Tom; Counsell, Nicholas; Patel, Rushil; Eaton, David; Faivre-Finn, Corinne; Fenwick, John; Forster, Martin; Hanna, Gerard G; Harden, Susan; et al.
Abstract : Introduction: Following growing evidence to support the safety, local control (LC) and potential improvement in overall survival (OS) in patients with oligometastatic non-small cell lung cancer (NSCLC) that have been treated with local ablative therapy such as stereotactic ablative radiotherapy (SABR) and stereotactic radiosurgery (SRS), we initiate the SARON trial to investigate the impact and feasibility of adding SABR/SRS and radical radiotherapy (RRT) following standard chemotherapy on OS. Methods and analysis: SARON is a large, randomised controlled, multicentre, phase III trial for patients with oligometastatic EGFR, ALK and ROS1 mutation negative NSCLC (1–3 sites of synchronous metastatic disease, one of which must be extracranial). 340 patients will be recruited over 3 years from approximately 30 UK sites and randomised to receive either standard platinum-doublet chemotherapy only (control arm) or standard chemotherapy followed by RRT/SABR to their primary tumour and then SABR/SRS to all other metastatic sites (investigational arm). The primary endpoint is OS; the study is powered to detect an improvement in median survival from 9.9 months in the control arm to 14.3 months in the investigational arm with 85% power and two-sided 5% significance level. The secondary endpoints are LC, progression-free survival, new distant metastasis-free survival, toxicity and quality of life. An early feasibility review will take place after 50 randomised patients. Patients requiring both conventional thoracic RT to the primary and SABR to a thoracic metastasis will be included in a thoracic SABR safety substudy to assess toxicity and planning issues in this subgroup of patients more thoroughly. Ethics and dissemination: All participants are given a SARON patient information sheet and required to give written informed consent. Results will be submitted for presentation at local and international conferences and expected to be published in a peer-reviewed journal. Trial registration number: NCT02417662. Sponsor reference: UCL/13/0594.